2017
DOI: 10.3389/fimmu.2017.01309
|View full text |Cite
|
Sign up to set email alerts
|

Global Assessment of Dengue Virus-Specific CD4+ T Cell Responses in Dengue-Endemic Areas

Abstract: BackgroundDengue is a major public health problem worldwide. Assessment of adaptive immunity is important to understanding immunopathology and to define correlates of protection against dengue virus (DENV). To enable global assessment of CD4+ T cell responses, we mapped HLA-DRB1-restricted DENV-specific CD4+ T cell epitopes in individuals previously exposed to DENV in the general population of the dengue-endemic region of Managua, Nicaragua.MethodsHLA class II epitopes in the population of Managua were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
83
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 49 publications
4
83
2
Order By: Relevance
“…However, the source of such massive production of cytokine remains elusive. On the other hand, the majority of the data regarding the physiology of T‐cells in dengue infection suggest a protective role, 5,7,30,31,49–52 but the innate source of this cytokinemia has been poorly investigated. Some data suggest that mast cells 53–55 and macrophages, 56,57 for example, may contribute to early cytokine production and also to severe dengue presentation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the source of such massive production of cytokine remains elusive. On the other hand, the majority of the data regarding the physiology of T‐cells in dengue infection suggest a protective role, 5,7,30,31,49–52 but the innate source of this cytokinemia has been poorly investigated. Some data suggest that mast cells 53–55 and macrophages, 56,57 for example, may contribute to early cytokine production and also to severe dengue presentation.…”
Section: Discussionmentioning
confidence: 99%
“…In previous experiments, we showed that pools based on similar peptide numbers can be generated by sequential lyophilization (Carrasco Pro et al, 2015). These peptide pools (or megapools) incorporate predicted or experimentally validated epitopes and allow measurement of magnitude and characterization of the phenotype of human T cell responses in infectious disease indications such as Bordetella pertussis, Mycobacteria tuberculosis, Dengue, and Zika viruses (Carrasco Pro et al, 2015;da Silva Antunes et al, 2018;Grifoni et al, 2017Grifoni et al, , 2018. The SARS-CoV-2 CD4 megapool covers all 10 predicted proteins, with the number of potential epitopes proportional to the size of each protein (Table S4).…”
Section: Prediction Of Sars-cov-2 T Cell Epitopesmentioning
confidence: 99%
“…74 The immunodominant epitopes recognized by CD4 + and CD8 + T cells have been mapped, with CD8 + T cells preferentially targeting NS proteins, such as NS3, NS4b and NS5; and CD4 + T cell responses toward structural proteins and NS1. [91][92][93] Both CD4 + and CD8 + T cell responses have been suggested to mediate protection in animal models or DENV-infected patients (see reviews 65,74,94,95 ). Like B cell immunity, cellular immune responses against DENV can be also cross-reactive against multiple DENV serotypes due to the similarity of genomic sequences.…”
Section: (Un) Balanced T Cell Immunity Of Latv Dengue Vaccinementioning
confidence: 99%